Literasi Pajak Pertambahan Nilai (PPN) dan Perilaku Konsumtif pada Generasi Z - Joko Sustiyo (Owner : Riset dan Jurnal Akuntansi, 2022)
Research on the impact of VAT literacy on consumptive behavior has not been studied in Indonesia. Most studies link financial literacy to consumptive behavior. To find out whether VAT literacy has an effect on consumptive behavior, this study uses simple linear regression analysis. The validity and reliability of the questionnaire instrument was confirmed first, which resulted that all questions on the questionnaire were valid and reliable. Then, the classical assumption test was carried out to ensure that the linear regression model was reliable which concluded that the data were normally distributed and there was no heteroscedasticity. Simple linear regression analysis shows that the predictor has a negative and significant effect on the consumptive behavior of Generation Z. The coefficient value of -1.130 indicates that an increase in VAT literacy by 1 point will reduce the consumptive behavior of Generation Z by 1.130 points. In other words, someone who knows and understands the VAT regulations will have the potential to reduce the consumption of goods and services.